Vermicompost and trichoderma in the development of cherry group tomato seedlings - Silva, Nayra Grazielle; Mambrí, Ana Paula de Souza; Santos, Dhylan Keillor Queiróz dos; Lopes, Sidnei José; Marques, Anderson Cesar Ramos; Silva, Antonio Carlos Ferreira da (Ciência e Natura, 2020)
Trichoderma is used as crop growth promoters. However, they may have harmful effects at higher concentrations. The objective of this work was to evaluate the vermicompost effect formulated with different concentrations of sandy soil, bioenriched with higher than recommended doses of trichoderma, on the germination, initial development and chemical composition of the cherry tomato Creole shoot. The treatments (T) used were substrate composed of vermicompost and sandy soil at 25 kg kg-1 (low), 50 kg kg-1 (medium) and 75 kg kg-1 (high), respectively. The Ecotrich bioproduct was added to the substrate at the following concentrations T1) 0.0; T2) 108; T3) 109; T4) 1010 cfu L-1. Afterwards, three cherry tomato seeds were sown per cell in trays containing the mixture, totaling 90 seeds per treatment. At 30 DAS, height, stem diameter, chlorophyll a, b and total, fresh and dry root and shoot phytomass, root volume and area, leaf area and leaf chemical analysis were evaluated. Bioproduct concentrations, compared to control without trichoderma, did not provide superior results for shoots and roots at 30 DAS. However, plants cultivated with higher concentration of vermicompost were less negatively affected at higher doses of the bioproduct.